Thomas Hare and Political Representation in Victorian Britain - Parsons, F. author. aut Link
X, 287 p.
Keywords: This book is a history of the emergence and development of the concept of proportional representation and its relation to political theory within the context of nineteenth-century British party politics focusing on Thomas Hare (1806-1891).